2008
DOI: 10.1159/000144029
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of Intraocular Lens Calculation Using the Holladay II Formula after in-the-Bag or Optic Captured Posterior Chamber Intraocular Lens Implantation in Paediatric Cataracts

Abstract: Purpose: To assess the predictability of postoperative refraction using the Holladay II-formula in paediatric patients randomized to undergo 2 different surgical procedures. Methods: Fourty cataractous eyes of 29 patients (age 2.31–11.75 years) were operated with in-the-bag intraocular lens implantation. Randomly, either an anterior vitrectomy (group A, 19 eyes) or posterior optic capture without vitrectomy (group B, 21 eyes) was performed. Randomization was done in 4 separate age groups, in accordance with 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Neely et al 4 reported a mean prediction error of 0.3 G 1.5 D. These authors further report that of the 4 formulas studied (SRK II, SRK/T, Holladay 1, and Hoffer Q), there was no evidence to Holladay 1 had the least error followed by the Holladay 2. The Hoffer Q and SRK/T formulas had equal mean absolute prediction error; however, the median error was less using the Hoffer Q. L€ uchtenberg et al 7 assessed the predictability of the postoperative refraction using the Holladay 2 formula in pediatric patients randomized to the optic capture procedure versus no optic capture. The Holladay 2 formula provided reliable IOL calculation in pediatric cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…Neely et al 4 reported a mean prediction error of 0.3 G 1.5 D. These authors further report that of the 4 formulas studied (SRK II, SRK/T, Holladay 1, and Hoffer Q), there was no evidence to Holladay 1 had the least error followed by the Holladay 2. The Hoffer Q and SRK/T formulas had equal mean absolute prediction error; however, the median error was less using the Hoffer Q. L€ uchtenberg et al 7 assessed the predictability of the postoperative refraction using the Holladay 2 formula in pediatric patients randomized to the optic capture procedure versus no optic capture. The Holladay 2 formula provided reliable IOL calculation in pediatric cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…They report a mean absolute prediction error of 1.40 D. Nihalani and VanderVeen 20 report a mean absolute prediction error of 0.76 D using the Holladay 1 formula. L€ uchtenberg et al 21 assessed the predictability of postoperative refraction using the Holladay II formula in pediatric patients randomized to an optic-capture versus a no-optic-capture procedure. The Holladay II formula provided reliable IOL calculations in pediatric cataracts.…”
Section: Resultsmentioning
confidence: 99%
“…6,50 as an example, the als in these children at time of surgery varied from There is also controversy noted in the literature regarding the most accurate formula for the pediatric eye undergoing implantation of an iol. [48][49][50][51][52][53][54][55][56][57][58] With improvements in surgical technique, ongoing improvements in iol design, and surgical instrumentation, our ability to implant in small eyes and very young children has been realized, and will hopefully continue to advance. however, the ability to calculate the appropriate iol power for any given pediatric eye is still not accurate and consistent enough in all circumstances, unlike that seen in adult iol power calculations.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the standard, well-tested regression and theoretical formulas used in adults are still the only tools available to pediatric cataract surgeons at present. as many others have noted, [48][49][50][51][52][53][54][55][56][57][58] a consistently accurate pediatric iol formula is needed that addresses all of the concerns and potential inaccuracies discussed in this article. until such controversy is resolved, we would suggest that a theoretical formula such as SRK/T or holladay 1 will probably give the most accurate results for most children undergoing cataract surgery with an iol.…”
Section: Discussionmentioning
confidence: 99%